OPTIMALISASI PERAN TENAGA TEKNIK KEFARMASIAN (TTK) PADA PELAKSANAAN SWAMEDIKASI VITAMIN SEBAGAI PENGUAT SISTEM IMUN DIMASA PANDEMI COVID-19 - Ika Kurnia Sukmawati; Ida Lisni; Ni Nyoman Mas Dri Hartini; Akhmad Pryadi; Ed Yunisa (Jurnal Abdi Masyarakat Kita, 2021)
Many people do self-medication to deal with complaints or symptoms of disease by buying drugs at a pharmacy or drug store. Such treatment needs to be carried out appropriately, so that people need clear information in determining the type and amount of drugs to be used rationally and how to use them properly. To be able to increase the understanding of Pharmaceutical Technical Workers in providing self-medicating vitamins as a booster for the immune system during the Covid 19 pandemic, community service was carried out by holding online webinars about vitamin giving material and its classification and characteristics of vitamins, as well as reminding about dosages, indications, side effects and the dangers of overuse of vitamins. In addition, an example video is provided for the provision of vitamin information to help technical understanding of pharmaceutical technical workers in providing drug information services to patients / the public. The webinar was held in two meetings, namely on 19 and 26 September 2020 with presenters being lecturers at the Faculty of Pharmacy, Bhakti Kencana University, to Pharmaceutical Engineering Workers who are members of the JABAR Indonesian Pharmacists Association (PAFI) organization. Community Service Activities through Webinars and screening of vitamin self-medication videos can increase understanding of Pharmaceutical Technical Staff in providing self-medicated vitamins as a booster for the immune system during the Covid 19 pandemic.